Dynamics of Shear Bands in a Dense Granular Material Forced by a Slowly Moving Rigid Body - Melo-Hurtado, F; Hamm-Hahn, L (2011)
We experimentally investigate the flow field in plane geometry around a slowly moving rigid finger in a dry, randomly packed granular medium. The finger enters the medium vertically from its free surface, in analogy with indentation tests on ductile materials. By developing a particle imaging velocimetry technique, we identify a localized flow around the finger, limited by two nearly symmetric shear bands that nucleate near the fingertip and reach the free surface of the granular compact. Evolution of the shear bands is discontinuous, exhibiting nucleation-relaxation processes as the finger moves downward. We present a simple model accounting for the shape of the shear bands at early stages of nucleation. We measure the force applied by the finger and the sources of dilation as well. A mechanism that relates local dilations to the total volume increase of the medium is proposed. © 2011 American Physical Society.